TEACHERS’ STRATEGIES IN OVERCOMING STUDENTS’ ANXIETY IN SPEAKING ENGLISH - Irmayani; Nunung Anugrawati; Andi Bulkis Maghfirah Mannong (Indonesian Journal of Psycholinguistics, 2022)
This research aimed to find out the teachers’ strategies in overcoming student’ anxiety in speaking English and students’ perception toward the strategies used by the teacher to overcome student’ anxiety in speaking English at SMAN 1 Gowa. This research was a descriptive qualitative research. The data was collected through observation checklist and semi-structured interview. The participants were the English teachers and students of at SMAN 1 Gowa. The researcher took 6 students from 3 classes; the X IPS1, XI IPA1, and XII IPA5 class and there English teachers.The findings showed about the teachers’ strategies to overcome students’ anxiety in speaking English and students’ perceptions toward the strategies used by the teachers. First, there were three strategies that were used by the teachers. The teacher who teaches at X IPS1 (T1) used playing games strategy, the teacher two who teaches at XI IPA1 (T2) used question and answer strategy, and the last teacher who teacher at XII IPA5 (T3) used guess word strategy in overcoming students’  anxiety in speaking English. Second, every single students who became respondents in this research said that they agree with the strategies used by the teacher can overcome their anxiety in speaking English.